Site Characteristics More Than Vegetation Type Influence Food Web Structure of Intertidal Salt Marshes - Lafage, Denis; Carpentier, Alexandre; Duhamel, Sylvain; Dupuy, Christine; Feunteun, Eric; Lesourd, Sandric; Pétillon, Julien (Frontiers in Marine Science, 2021)
Salt marshes are under increasing anthropogenic pressures which have been reported to affect the diet of fish (e.g. change of preys, prey accessibility), as a result of alterations in their nursery function. Most studies in Europe are based on fish gut content analysis, which only reflect a small proportion of pressures to salt marshes, and do not necessarily reflect long-term disturbances. In this study, we investigated the impact of salt-marsh vegetation type on trophic network structures (i.e. fish diet and trophic position). Primary producers (particular organic matter, microphytobenthos and dominant terrestrial plants), potential aquatic and terrestrial prey, and fish of two dominant species (sea bass and thinlip mullet) were sampled during the summer of 2010 in four creeks from two sites from Western France (the Mont-Saint-Michel Bay and the Seine Estuary). Analysis was undertaken using C and N stable-isotope compositions. Tested response variables (diet and trophic position) suggested a dominant site effect and a weaker effect of surrounding vegetation type. Site effect was attributed to differences in anthropogenic nitrogen inputs and tidal regime between the two bays, with more marine signatures associated with a higher frequency and duration of tidal flooding events. A second hypothesis is that invasive Elytrigia acuta, which has recently replaced typical salt-marsh vegetation in Mont-Saint-Michel Bay, negatively impacted the native salt-marshes nursery function. The trophic position of the sea bass and the thinlip mullet was unchanged by local salt-marsh vegetation, and considered consistent with their diet. This study highlights the relevance of stable-isotopes analyses for assessing long-term and integrative effects of changes in vegetation resulting from human disturbances in salt marshes.